Effect of Petrogenic Fertilizer Dosage with Different Seed Sources on the Growth and Production of Onion (Allium ascalonicum L.) - Sakinah Padang; Iswahyudi Iswahyudi; Cut Mulyani (University of Prof. Dr. Hazairin, SH, 2023)
The study aimed to determine the effect of Petroganic fertilizer doses and seed sources on the growth and production of onion plants and to determine the interaction between the two. This study used 2 factorial shelves, petroganic (P) fertilizer dosage consisting of 4 levels, namely P0 = control, P1 = 10 gr/ polybag, P2 = 20 gr/polybag, P3 = 30 gr/ polybag, and different seed source factors consisting of 2 levels, namely B1 = seed TSS varieties Sanren F1 and B2 = seed tubers varieties Bima Brebes. Parameters observed were plant height, number of leaves, number of bulbs per clump, wet weight of bulbs per sample, and per plot. Petroganic fertilizer dose significantly affects plant height and number of leaves at the age of 40 and 60 HST, tuber weight per sample, and per plot. However, no real effect on plant height and number of leaves aged 20 HST, as well as the number of bulbs per clump. The best results were obtained in the P3 treatment. Treatment of seed sources significantly affected the plant height and number of leaves aged 40 and 60 HST, the number of tubers per clump, the wet weight of tubers per sample, and per plot. The best results were obtained in the B2 treatment. The interaction between the two had a significant effect on the parameters of the wet weight of tubers per plot. The best results were obtained in the combination of petroganic P3 fertilizer dosage treatment with B2 seed source.